Fully bonded iron-based shape memory alloy for retrofitting large-scale bridge girders: thermal and mechanical behavior - Wang, Sizhe (2024)
This study presents a prestressed retrofitting solution for addressing fatigue issues in large-scale steel girders, employing iron-based shape memory alloy (Fe-SMA) strips and adhesive bonding. A comprehensive study encompassing design, experimental tests, and numerical analysis is conducted to develop and validate the proposed solution. A 4200×100×1.5 mm Fe-SMA strip is fully bonded along its entire surface using a two-component epoxy adhesive to a 5300 mm span steel girder. An activation strategy to prestress the Fe-SMA strip is formulated based on a series of finite element (FE) analyses, entailing successive block-by-block heating using a gas torch. Experimental and numerical studies illuminate the full-range thermal and mechanical behavior of the retrofitted girder throughout the activation process. A FE heat transfer analysis with experimental validation reveals the temperature developments and distributions during activation, highlighting a 160 ℃/mm temperature gradient along the adhesive thickness and longitudinal distributions with localized high temperatures. The mechanical behavior during activation, encompassing the effects of thermal expansion, Fe-SMA prestress, and adhesive softening and re-hardening, is interpreted based on experimental and numerical results, showing the evolutions and distributions of deflections, strains, and Fe-SMA prestresses. Static tests and a high-cycle fatigue test up to 3 million load cycles demonstrate the effectiveness and structural integrity of the proposed retrofitting solution.